2008
DOI: 10.1159/000128582
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA Expression of Antimicrobial Peptides and Proteins in Atopic Dermatitis as Compared to Psoriasis Vulgaris and Healthy Skin

Abstract: Background: Patients with atopic dermatitis (AD) are prone to have skin infections. We aimed to investigate mRNA expression levels of various antimicrobial peptides and proteins (AMPs) in AD patients, and compare it with psoriasis vulgaris (PV) patients and healthy subjects. Methods: Skin biopsies were obtained from healthy subjects and patients with AD and PV. Quantitative real-time RT-PCR was used to determine the mRNA levels of human β-defensin (hBD)-1, hBD-2, hBD-3, LL-37, psoriasin, RNase 7, interferon-γ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 40 publications
15
109
4
1
Order By: Relevance
“…Therefore, we first analyzed the expression of BDs (BD1, BD2, and BD3) and S100 proteins (S100A7, S100A8, and S100A9) in AI lesions and, as a comparison, in lesional skin from Ps and AD patients as well as in healthy skin from control participants. In line with previous results from others and ourselves (8,14,15,17,(20)(21)(22)(23), we found constitutive AMP expression in healthy skin and a strong upregulation of all AMPs except of BD1 in lesions from Ps and AD patients (Fig. 1).…”
Section: Ai Skin Lesions Show a Relative Deficiency Of Ampssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we first analyzed the expression of BDs (BD1, BD2, and BD3) and S100 proteins (S100A7, S100A8, and S100A9) in AI lesions and, as a comparison, in lesional skin from Ps and AD patients as well as in healthy skin from control participants. In line with previous results from others and ourselves (8,14,15,17,(20)(21)(22)(23), we found constitutive AMP expression in healthy skin and a strong upregulation of all AMPs except of BD1 in lesions from Ps and AD patients (Fig. 1).…”
Section: Ai Skin Lesions Show a Relative Deficiency Of Ampssupporting
confidence: 93%
“…Apart from AI, AD also represents an inflammatory skin disease with frequent bacterial persistence in the affected skin (20)(21)(22)(23). We demonstrated in this study that, surprisingly, the extent of the relative AMP deficiency in AD was much lower than in AI.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2; P < 0.05, each). Although previous reports showed that hBD-1 expression correlated with disease activity in psoriasis (15,27), it was not elevated in lesional skin of psoriasis compared with normal skin. Of note, mRNA levels Figure 2.…”
Section: Resultscontrasting
confidence: 57%
“…Entdeckung von mehreren Arbeitsgruppen unabhängig bestätigt [49,50]. Neben Psoriasin sind auch viele weitere antimikrobielle Peptide (AMP) in der Psoriasishaut induziert, so zum Beispiel die humanen ␤-Defensine (hBD)-2 und -3, das Cathelicidin LL-37 und Calprotectin (ein Komplex aus den S100-Proteinen A8 und A9).…”
Section: Die Erhöhte Expression Von Psoriasin Bei Patienten Mit Psoriunclassified